(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2017)
This paper contains the main changes lived in the Economy, the Law and the corporations, as a result of an inquiry done to experts of different institutions, universities and companies. It also includes the changes that are necessary to do in the short term.